GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2017)
A dataset containing 19458 species occurrences available in GBIF matching the query: TaxonKey: Bubo bubo (Linnaeus, 1758). The dataset includes 19458 records from 202 constituent datasets: 12 records from Ghent University - Zoology Museum - Vertebrate collection. 1 records from SUI Vertebrate Collection. 1 records from Australian National Wildlife Collection provider for OZCAM. 12 records from Ornithology Collection Non Passeriformes - Royal Ontario Museum. 7 records from Zoology (Museum of Evolution - Uppsala). 118 records from PlutoF platform observations. 2128 records from Inventario Español de Especies Terrestres (MAGRAMA). 79 records from The avian collection at the Natural History Museum, Oslo, Norway. 2 records from BioFokus. 47 records from Field Museum of Natural History (Zoology) Bird Collection. 2 records from Museum Victoria provider for OZCAM. 1 records from Eggs Specimen. 8 records from The atlas of breeding birds in Małopolska. 96 records from Lund Museum of Zoology (MZLU). 438 records from Données ONF Faune-Flore-Fonge. 3 records from Field Museum of Natural History (Zoology) Bird Egg Collection. 1 records from UAM Bird Collection (Arctos). 12 records from Norwegian Biodiversity Information Centre - Other datasets. 59 records from Museum of Comparative Zoology, Harvard University. 7 records from CAS Ornithology (ORN). 2218 records from Bird Ringing Centre in Sweden (NRM). 1091 records from EOD - eBird Observation Dataset. 25 records from iNaturalist Research-grade Observations. 392 records from Aranzadi Ringing Scheme (bird ring-recovery data). 2 records from Birds collection of Abiko City Museum of Birds. 8 records from Birds collection of Yamashina Institute for Ornithology. 1 records from Musée Vert ornithology collection. 18 records from Estonian Museum of Natural History. 343 records from Inventaire National du Patrimoine Naturel : Oiseaux nicheurs de France. 1 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Aves (MFA-ZV-Or). 1 records from Birdrace-Brut-Wetteraukreis. 1 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 1 records from Birdrace_Gütersloher_Gimpel-Gütersloh. 2 records from Literature based species occurrence data of birds of North-East India. 1 records from Birdrace-Uhulogen-Lippe. 1 records from Birdrace-Team_Charadrius-Günzburg. 1 records from Birdrace-Diesmal_sehen_wir_mehr-Lippe. 1 records from Birdrace-Herford-Birder-Herford. 1 records from Birdrace-Die_EderSeaWatchers_WsndaH!-Waldeck/Frankenberg. 1 records from Birdrace-Die_Bonnapartemöwen-Rhein-Sieg-Kreis. 1 records from Birdrace-federleser-Herford. 1 records from Birdrace-Buteo1_DO-Dortmund. 1 records from Birdrace-Die_TUErteltauben-Tübingen. 1 records from Birdrace-Team_BO-bachter-Bochum. 1 records from Birdrace-Enger_am_Spektiv-Herford. 1 records from Birdrace-Die_Paradiesvögel-Herford. 2 records from Birdrace_Schräge_Vögel-Herford. 2 records from Birdrace-Die_Nachtigallen-Herford. 1 records from Birdrace-Buteo2DO-Dortmund. 1 records from Birdrace-Haubenpirole_vom_Biomarkt_West-Tübingen. 1 records from WildesMoor bei Schwabstedt. 1 records from Waldstück Bremerhagen LK Bio Kl. 12. 1 records from Birdrace-Alb_Donaumoos_Kompetänzteam-Alb-Donau-Kreis. 1 records from Birdrace-Göttinger_Sozialbrachvögel-Göttingen. 1 records from Birdrace-The_early-Birds-Minden/Lübbecke. 1 records from Birdrace-ImmerWiederhopf-Lörrach. 1 records from Birdrace-Die_Vogelscheuchen-Herford. 1 records from Birdrace-Die_Ornithomaten-Herford. 1 records from Vögel. 1 records from Trockenmauern am ehemaligen Weinberg (Gelnhausen). 2062 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Aves Reproductoras. 2 records from BIRDRACE Gätkes Erben. 1 records from BIRDRACE Dith Marsh Sandpiper. 2 records from BIRDRACE Pody und Co. 2 records from BIRDRACE Alb-Donaumoos-Kompetänzteam. 1 records from BIRDRACE Die Ziegeneier. 1 records from BIRDRACE Die Düsselmöwen. 1 records from BIRDRACE NABU LV Hessen. 1 records from BIRDRACE SchrägeVögel. 1 records from BIRDRACE NABUhu Trier!. 1 records from BIRDRACE Die Paradiesvögel. 1 records from BIRDRACE TEAM BO-BACHTER. 1 records from BIRDRACE Enger am Spektiv. 1 records from BIRDRACE federleser. 1 records from BIRDRACE Die Otzberger. 1 records from BIRDRACE Bon(n)apartemöwen. 1 records from BIRDRACE Die Wetterauer. 1 records from BIRDRACE Brut. 1 records from BIRDRACE Duckehühnchen. 1 records from BIRDRACE The early birds. 1 records from BIRDRACE Die UHULOGEN. 1 records from BIRDRACE Gütersloher Gimpel. 1 records from BIRDRACE Diesmal sehen wir mehr. 1 records from BIRDRACE Herford Birders. 1 records from BIRDRACE Borussia Zippammer. 1 records from Liether Kalkgrube. 2 records from BIRDRACE Dithmarscher Deichhühner. 1 records from BIRDRACE Nachtigallen. 1 records from BIRDRACE Blinde Hühner. 2 records from BIRDRACE Die Schwenker-Birder. 1 records from BIRDRACE Ornis im Einsatz. 1 records from BIRDRACE Die TUErteltauben. 1 records from BIRDRACE Mathilden-Käuze. 1 records from BIRDRACE Vogelscheuchen. 1448 records from naturgucker. 9 records from Vertebrats d'Andorra. 1 records from Artenvielfalt im Rhein-Neckar-Raum. 3 records from BIRDRACE Die Kielbris. 57 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 104 records from Museu de Ciències Naturals de Barcelona: MCNB-Cord. 6 records from Bird Specimens in the Museum of Nature and Human Activities, Hyogo, Japan. 1 records from SBMNH Vertebrate Zoology. 2 records from LACM Vertebrate Collection. 4 records from Natural History Museum Rotterdam (NL) - Chordata collection. 1 records from BIRDRACE Bergische Ornis. 1 records from BIRDRACE HGON Kelkheim-Rumpfteam. 2 records from Birds (JNHM-BI). 20 records from Birds (KIEE-BI). 2 records from Birds (ENHM-BI). 21 records from Birds (NSMK-BI). 1 records from Birds (GMBO-BI). 5 records from Collection Ornithologie - ZSRO. 4 records from Estación Experimental de Zonas Áridas (CSIC) EEZA - Aves. 7 records from SysTax - Zoological Collections. 13 records from Birds (NHCA-BI). 59 records from Natural History Museum (London) Collection Specimens. 7 records from Inventario Fauna Vertebrada de la Manchuela Conquense (CUENCA), 2007. Asociación de Desarrollo Integral de la Manchuela Conquense (ADIMAN). 3 records from Macaulay Library Audio and Video Collection. 1 records from Field Study Group of the Dutch Mammal Society (NL) - 2006 - Mammal Survey Galicica National Park, Macedonia. 2 records from Ibaraki Nature Museum, Birds collection. 51 records from NMNH Extant Specimen and Observation Records. 15 records from Collection Ornithologie - SNSD. 4 records from UWBM Ornithology Collection. 914 records from Inventaire National du Patrimoine Naturel : Oiseaux hivernants de France. 65 records from Museo Nacional de Ciencias Naturales, Madrid. Colección de Tejidos y ADN. 40 records from Museo Nacional de Ciencias Naturales, Colección de Aves: MNCN-Ornit. 1 records from Bird Collection of Otto Hedin. 2 records from Mammalia - Baekdu Mountain Animal (KIDR-MM). 14 records from Birds - Wild Birds (KIDR-BI). 2 records from Provincial Museum of Alberta, Edmonton, AB, Canada. Birds (Aves). 1 records from Paleobiology Database. 4 records from LSUMZ Birds Collection. 4 records from Bird collection of National Museum of Nature and Science. 2 records from SDNHM Birds Collection. 1 records from CNAV/Coleccion Nacional de Aves. 8 records from Vertebrate Zoology Division - Ornithology, Yale Peabody Museum. 966 records from Biologiezentrum Linz. 461 records from Israel Nature and Parks Authority. 588 records from VerteCAT: Banco de datos de vertebrados de Cataluña. 730 records from inatura - Erlebnis Naturschau Dornbirn. 12 records from ORN. 25 records from Aves MZS. 1 records from Bird specimens in Gifu Prefectural Museum. 101 records from Biodiversitätsdatenbank des Landes Salzburg. 74 records from Naturalis Biodiversity Center (NL) - Aves. 1 records from Schule Sulzbach (Oberegg). 1 records from Artenvielfalt auf der Weide - GEO-Hauptveranstaltung in Crawinkel. 1 records from Fels- und Weinbergsflächen in Hatzenport/Terrassenmosel. 1 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 1 records from Himmelmoor. 1 records from Birdrace_MarschPIeper_Pinneberg. 1 records from Birdrace-SpeedBirder-Zwickauer_Land. 1 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - Birdrace-Pody&Co.-Plön. 1 records from Birdrace-Easy_Birders-Plön. 21 records from WFVZ Bird Collections. 2 records from Natural History Museum, University of Tartu. 526 records from Banco de Datos de la Biodiversidad de la Comunitat Valenciana. 85 records from Vertebrate specimens of Jyväskylä University Museum. 17 records from Biological and palaeontological collection and observation data MNHNL. 5 records from Collection Aves (spirit preserved) SMF. 47 records from Collection Aves (bird skeletons) SMF. 72 records from Collection Aves (bird skins) SMF. 84 records from AMNH Bird Collection. 10 records from Birds (KIDR-BI). 12 records from Birds (KNAM-BI). 288 records from BioGIS - Birds - INPA database. 7 records from Bird Collection of Helsingborgs Museum. 1 records from MVZ Egg and Nest Collection (Arctos). 6 records from Ornitho.eus. 3 records from Inventaire National du Patrimoine Naturel : Inventaire du Parc national du Mercantour. 1 records from Collection ornithologique A. Maës. 2 records from Queensland Museum provider for OZCAM. 9 records from CM Birds Collection. 293 records from ArtenFinder. 2 records from Auckland Museum Land Vertebrates Collection. 5 records from Geographically tagged INSDC sequences. 505 records from Norwegian Species Observation Service. 2 records from Biodiversity Research and Teaching Collections - TCWC Vertebrates. 36 records from Animal Sound Archive. 46 records from The birds collection (ZO) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 12 records from UMMZ Birds Collection. 14 records from Aves Collection of Institute of Systematics and Evolution of Animals. 63 records from Estonian Nature Observations Database. 1228 records from EBCC Atlas of European Breeding Birds. 2 records from FNJV - Fonoteca Neotropical Jacques Vielliard. 23 records from Ájtte. 438 records from Données ONF Faune-Flore-FOnge. 3 records from Caire-Chabrand Collection. 1 records from Vegetation data from protected areas in Denmark (§ 3 in the Danish Nature Protection Act). 18 records from National System of Protected Areas in Poland - Animals. 8 records from MVZ Bird Collection (Arctos). 1 records from KUBI Ornithology Collection. 5 records from Suffolk Biodiversity Information Service (SBIS) Dataset. 1 records from Collection scientifique et pédagogique de l'Ecole Normale Supérieure de Lyon. 357 records from Vertebrates of the Gothenburg Natural History Museum (GNM). 3 records from Kieppi bird collection. 20 records from Data collected on scitizen science web portal www.ornitho.cat. 3 records from BRERC species records within last 15 years. 3 records from CUMV Bird Collection (Arctos). 2 records from South Australian Museum Australia provider for OZCAM. 2 records from LSUMZ Bird Tissues. 19 records from Bird Collection of Museum and Institute of Zoology PAS. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences